Insights on luminescence quenching of ZnO tetrapods in the detection of hCG - Rodrigues, J. (2021)
Metal oxide semiconductors, and particularly zinc oxide (ZnO), are amongst the most investigated materials to be applied as transducer elements in biosensing devices due to properties as biochemical stability, biocompatibility and functionalisation simplicity. In the present work, ZnO nanotetrapods were produced by the laser-assisted flow deposition technique to be used as transducers in a photoluminescence (PL)-based immunosensor to detect the human chorionic gonadotropin (hCG) hormone. The produced nanostructures were analysed by electron microscopy, Raman and PL spectroscopies. The ZnO tetrapods exhibit an intense PL in both the ultraviolet and visible range, whose intensity changed after the direct immobilisation of the anti-hCG antibodies into the semiconductor’s surface. The changes in the PL intensity after the interaction of the immobilised antibodies with hCG were used as the transduction mechanism for the envisaged sensors. It was observed that when antibody-antigen interactions occur, charge rearrangement at the surface of the semiconductor leads to a reduction in overall intensity of the PL signal with increasing hCG concentration, allowing to establish a correlation between the PL output and the probed concentration. Therefore, such behaviour suggests the adequacy of the developed ZnO-based transducers to be incorporated into optical biosensors. Additionally, the possible interaction mechanisms between the ZnO surface and the immobilised molecules responsible for the changes in the PL spectra were discussed.